2015
DOI: 10.1097/igc.0000000000000468
|View full text |Cite
|
Sign up to set email alerts
|

Sexual Activity and Function in Patients With Gynecological Malignancies After Completed Treatment

Abstract: A high number of patients with GC remain sexually inactive after treatment, indicating that women experience persistent functional problems. However, women who regain SA after completed treatment have a good overall SF and vice versa.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
12
4
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 37 publications
5
12
4
1
Order By: Relevance
“…These effects of cancer treatment may have contributed to our participants’ sexual dysfunction. Indeed, more than half of our participants (55.8%) were not sexually active after completing treatment, similar to the finding that only 41.3% of German women were sexually active after completing treatment for gynaecological cancer compared to 78% of healthy women in the control group (Grimm et al., ).…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…These effects of cancer treatment may have contributed to our participants’ sexual dysfunction. Indeed, more than half of our participants (55.8%) were not sexually active after completing treatment, similar to the finding that only 41.3% of German women were sexually active after completing treatment for gynaecological cancer compared to 78% of healthy women in the control group (Grimm et al., ).…”
Section: Discussionsupporting
confidence: 89%
“…were not sexually active after completing treatment, similar to the finding that only 41.3% of German women were sexually active after completing treatment for gynaecological cancer compared to 78% of healthy women in the control group (Grimm et al, 2015).…”
Section: Discussionsupporting
confidence: 79%
“…8 In the present study, we noted a sexual inactivity rate of 55.9% among patients with EC but do not have any information for comparison, and the most common reason for a lack of intercourse was a ''psychological problem'' (30.8%). Zeng et al 22 reported a high sexual inactivity rate of 70.5% after they investigated 156 Chinese women with gynecological cancer.…”
Section: Discussioncontrasting
confidence: 61%
“…Similarly, a majority of studies limits participation to a restricted age range; as a result, little is known of sexual dysfunction in women over the age of 60 (Bae & Park, 2016;Bennett et al, 2016;Farthmann et al, 2016;Stead et al, 2003). A more robust understanding of the impacts of sexual dysfunction on the lives of single, non-partnered cancer patients and survivors is also needed, as this population has received relatively little focus within the literature to date (Donovan et al, 2007;Grimm et al, 2015;Philip et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Sexual wellbeing is affected by cancer and its treatments through a variety of interacting biopsychosocial pathways (Bae & Park, 2016;Boquiren et al, 2016;Carpenter, Andersen, Fowler, & Maxwell, 2009;Cull et al, 1993;Grimm et al, 2015). In women treated for diverse cancer diagnoses, issues related to sexual desire, arousal, orgasm, lubrication and pain often interfere with sexual function and are accompanied by significant distress (Denlinger et al, 2014;Falk & Dizon, 2013;Stead et al, 2007).…”
Section: Impacts Of Cancer and Its Treatment On Sexual Wellbeingmentioning
confidence: 99%